(untitled) (Medical Forum Monthly, 2020)
Objective: The objectives of the study were to evaluate the morphological changes observed in aminoglycoside (Amikacin) induced nephrotoxicity in rabbits and their attenuation by concomitant administration of Alpha tocopherol and selenium in animal model. Study Design: Experimental study Place and Duration of Study: This study was conducted at the Department of Pharmacology, Azra Naveed Medical College, Lahore for the duration of six months. Materials and Methods: Twenty-four rabbits were divided equally into four groups. Group 1 being control group was given 2ml of isotonic solution while group 2 was induced nephrotoxicity by giving Amikacin 150 mg/kg body weight daily for 20 days intramuscularly twice a day. Group 3 Amikacin was given along with alpha tocopherol (1g/kg body weight) and selenium (2mg/kg body weight) Intramuscularly for the same study period. Group 4 was given only alpha tocopherol and selenium in above doses. At the end of study, histopathology of kidney tissues was evaluated and morphological changes were noted. Results: Histological evaluation showed that Amikacin produced degenerative changes in proximal tubules causing interstitial infiltration and vascular congestion which were later on histologically seen to be minimized by giving treatment with alpha tocopherol and selenium. Conclusion: It was concluded that morphological changes induced by Amikacin were attenuated when alpha tocopherol & selenium were co-administered in specific doses.